2018
DOI: 10.1021/acs.biochem.7b01130
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Calmodulin with the cSH2 Domain of the p85 Regulatory Subunit

Abstract: Calmodulin (CaM) is a calcium sensor protein that directly interacts with the dual-specificity (lipid and protein) kinase PI3Kα through the SH2 domains of the p85 regulatory subunit. In adenocarcinomas, the CaM interaction removes the autoinhibition of the p110 catalytic subunit of PI3Kα, leading to activation of PI3Kα and promoting cell proliferation, survival, and migration. Here we demonstrate that the cSH2 domain of p85α engages its two CaM-binding motifs in the interaction with the N- and C-lobes of CaM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…For the second, we established the CaM–cSH2 complex using the HADDOCK server, 38 based on NMR data. 39 Candidates with an RMSD < 4 Å were classified into clusters. For each combination of the extended and collapsed CaMs in complex with nSH2 and cSH2 domains, four candidates with the highest docking scores were selected, generating a total of 16 configurations, configurations 1–16 (Figure S1 and Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…For the second, we established the CaM–cSH2 complex using the HADDOCK server, 38 based on NMR data. 39 Candidates with an RMSD < 4 Å were classified into clusters. For each combination of the extended and collapsed CaMs in complex with nSH2 and cSH2 domains, four candidates with the highest docking scores were selected, generating a total of 16 configurations, configurations 1–16 (Figure S1 and Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in a model proposed by Chaudhuri et al [154], activation of this tyrosine kinase by lysophosphatidylcholine results in the formation of phospho-Tyr99-CaM, which binds to the regulatory p85 α-subunit of PI 3 K, releasing its inhibitory action on the catalytic p110 subunit. Wang et al [155] later showed that binding of non-phosphorylated CaM to the C-terminal SH2 domain of p85 α-subunit led to PI 3 K activation. In addition, since CaM directly binds to p110 with high affinity this might be another way to regulate this lipid kinase [156].…”
Section: Cam-dependent Phosphorylationmentioning
confidence: 99%
“…K-RasB, but not H-Ras or N-Ras, binds to and is down-regulated by CaM [28]. Also, PI 3 K is regulated by CaM upon binding to its 110 kDa catalytic subunit (p110) [29] and the 85 kDa regulatory subunit (p85) [30]. Phospho-Tyr99-CaM, probably produced by a Src-family kinase, also interacts with the two SH2 domains of the regulatory p85 subunit of PI 3 K, activating in this manner its catalytic p110 subunit [31].…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 99%
“…K-Ras4B is represented in its GDP-bound conformation, and phospho-Tyr99 (-Tyr-P) CaM is highlighted. This theoretical model is based on reference [30], but it does not depict the actual interaction sites of the different proteins in the complex. The structures were obtained from PDB ID: 4L1B (human PI 3 K, full-length p110α and 318–615 amino acid segment of p85α, at 2.6 Å X-ray resolution [88,89]), 1CLL and 1CFC (human and Xenopus CaM at 1.7 Å X-ray resolution and NMR-derived structure, respectively [87,90]) and 4LDJ (human K-Ras4B at 1.15 Å X-ray resolution [91]).…”
Section: Phospho-tyr-cam In Pathophysiologymentioning
confidence: 99%